Binding S0.6Se0.4 in 1D Carbon Nanofiber with CS Bonding for High‐Performance Flexible Li–S Batteries and Na–S Batteries. Issue 19 (29th March 2017) - Yao, Yu; Zeng, Linchao; Hu, Shuhe; Jiang, Yu; Yuan, Beibei; Yu, Yan
Abstract : A one‐step synthesis procedure is developed to prepare flexible S0.6 Se0.4 @carbon nanofibers (CNFs) electrode by coheating S0.6 Se0.4 powder with electrospun polyacrylonitrile nanofiber papers at 600 °C. The obtained S0.6 Se0.4 @CNFs film can be used as cathode material for high‐performance Li–S batteries and room temperature (RT) Na–S batteries directly. The superior lithium/sodium storage performance derives from its rational structure design, such as the chemical bonding between Se and S, the chemical bonding between S0.6 Se0.4 and CNFs matrix, and the 3D CNFs network. This easy one‐step synthesis procedure provides a feasible route to prepare electrode materials for high‐performance Li–S and RT Na–S batteries. Abstract : A flexible S0.6 Se0.4 @carbon nanofibers (CNFs) electrode is prepared by coheating S0.6 Se0.4 powder with electrospun polyacrylonitrile nanofiber papers. The S0.6 Se0.4 @CNFs show excellent electrochemical performance for Li–S batteries and room temperature Na–S batteries, which attributes to the chemical bonding between Se and S, the chemical bonding between S0.6 Se0.4 and CNFs matrix, and the 3D CNFs network.